Management of Complex Root Canal Curvature of Bilateral Radix Entomolaris: Three-Dimensional Analysis with Cone Beam Computed Tomography. (21st December 2013) - Mahendra, Muktishree; Verma, Anand; Tyagi, Sanjeev; Singh, Santosh; Malviya, Kapil; Chaddha, Ramit
Abstract : The meticulous knowledge of anatomic characteristics and their variations is essential for the clinician. Radix entomolaris (RE) is one such anomaly where an extra root is present on the distolingual aspect of the mandibular first molar. 18-year-old patient was referred for the root canal treatment of mandibular right and left first molars. Intraoral periapical radiograph revealed additional periodontal spacing crossing distal root of 36. A CBCT was advised and it confirmed the presence of extra roots both in 36 and 46. CBCT is useful in endodontics as it aids in the identification of essential anatomic structures and determination of radius and angle of root canal curvature which is linked to fracture of the instrument. The classical triangular access cavity was modified to a trapezoidal form to locate the extra canal. All canals were instrumented with controlled memory nickel titanium instruments and obturation was done with single cone technique.